Macroalgae Ecology Index in Leuweung Sancang Nature Reserve Area - Aqilah, Siti; Rossa, Apriliana; Lubbiyah, Fanny Fairuz; Irpan, Aip Muhamad (Biosfer: Jurnal Tadris Biologi, 2024)
One of the many marine organisms in Indonesia is macroalgae. Macroalgae has many benefits as a raw material for industries such as food, textile, and cosmetic industries. Macroalgae also provide a habitat for several types of marine life, such as crustaceans, mollusks, echinoderms, and fish. This study aims to determine the diversity, dominance, and evenness in the Leuweung Sancang Nature Reserve Area. This study uses a survey method with data collection using the quadrant transect method. The results of the study showed that there were 11 species of macroalgae found in the Leuweung Sancang Nature Reserve, including Turbinaria ornate, Padina australis, Sargasum aquifolium, Sargasum polycystum, Ulva reticulate, Chaetomorpha crassa, Ulva lactuca, Boodlea composite, Amphiroa rigida, Amphiroa fragilissima, and Glacilaria coronopifolia. The value of the macroalgae diversity index in the Leuweung Sancang Nature Reserve is included in the medium category with an average value of 1.0573, the dominance index value is included in the low category with an average value of 0.4004, and the evenness index value is included in the low category with an average value of 0.2671. This research contributes to determining the density, frequency of occurrence, and diversity of macroalgae species.ABSTRAK: Organisme laut yang banyak di Indonesia salah satunya adalah makroalga. Makroalga memiliki banyak manfaat sebagai bahan baku industri seperti industri makanan, tekstil dan kosmetik. Makroalga juga menyediakan habitat untuk beberapa jenis biota laut seperti krustasea, moluska, echinodermata dan ikan. Penelitian ini bertujuan untuk mengetahui keanekaragaman, dominansi, dan kemerataan yang terdapat di Kawasan Cagar Alam Leuweung Sancang. Penelitian ini menggunakan metode survei dengan pengembilan data menggunakan metode transek kuadran. Hasil penelitian menunjukkan spesies makroalga yang ditemukan di Kawasan Cagar Alam Leuweung Sancang berjumlah 11 spesies diantaranya Turbinaria ornate, Padina australis, Sargasum aquifolium, Sargasum polycystum, Ulva reticulate, Chaetomorpha crassa, Ulva lactuca, Boodlea composite, Amphiroa rigida, Amphiroa fragilissima, dan Glacilaria coronopifolia. Nilai indeks keanekaragaman makroalga di Kawasan Cagar Alam Leuweung Sancang termasuk ke dalam kategori sedang dengan nilai rata-rata yaitu 1.0573, nilai indeks dominansi termasuk ke dalam kategori rendah dengan nilai rata-rata sebesar 0.4004 dan nilai indeks kemerataan termasuk ke dalam kategori rendah dengan nilai rata-rata sebesar 0.2671. Penelitian ini memberikan kontribusi dalam mengetahui kepadatan, frekuensi kemunculan dan keragaman jenis makroalga.